Sejarah Peninggalan Belanda di Sukadana Lampung Timur - Winata, Rian Surya (Yayasan Alpatih Harapan Semesta, 2023)
Writing this article aims to find out the history of Dutch heritage in the village of Sukadana, East Lampung. The method used is qualitative with a naturalistic paradigm. The research instruments are observation, interview guides, and researchers as key instruments. The data source for this research is the results of interviews with cleaning service officers at the puskesmas, village youth leaders and post office leaders. The result is that East Lampung Regency is one of the regencies resulting from the division in 1999. Sukadana is used as a place of transmigration or transfer of people or communities from Java. This migration or also known as colonization was carried out for the first time in November 1905 by bringing the first batch of colonization groups from Bagelen, Kedu Residency, Central Java, which were then placed in Gedong Tataan. The Dutch East Indies government moved people from Java and placed them in almost all areas in Lampung. This policy continued until 1979. As long as the Dutch Government was in Sukadana village they left several traces of historic buildings for the Sukadana community. These buildings include, namely, the old well, the staircase building, the head of state's building, and the post office. As well as the buildings on the Tamiang hill.